The spirit in first century Judaism - Levison, John R. (Arbeiten zur Geschichte des antiken Judentums und des Urchristentums, 1997)
Conceptions of the divine spirit underwent complex metamorphoses in Jewish biblical interpretation during the Greco-Roman era. This monograph explores those permutations in the writings of Philo Judaeus, Josephus, and Pseudo-Philo ( Liber Antiquitatum Biblicarum ). The first section, 'An Anomalous Prophet', unfolds surprisingly divergent transformations of the inspiration of Balaam. The second section, 'An Eclectic Era', unearths both faint and conspicuous traces of Greco-Roman conceptions in early Jewish interpretations. The third section, 'An Extraordinary Mind', undermines the view that the spirit was associated primarily with ecstasy rather than with intellectual insight. By analyzing these interpretations in light of other contemporary Greco-Roman and Jewish writings, this volume offers original and essential data for further study of inspiration in Antiquity, including early Judaism, early Christianity, and the Greco-Roman world. This publication has also been published in paperback, please click here for details.